Android translator App (Chinese to English) - Yeo, Yong Hua (2014)
An Android Translator Application focusing on Chinese to English translations based for Chinese Tourists visiting Singapore. Features includes SQLite Database offline output, as well as Microsoft Bing Translator Direct Translation.